Culture standards and their impact on teamwork: An empirical analysis of Austrian, German, Hungarian and Spanish culture differences - Amanda Dunkel; Sylvia Meierewert (Journal for East European Management Studies, 2004)
This article examines the impact of different cultural standards on the processes and performances of Austrian, Spanish, German and Hungarian task groups. We therefore analyzed 201 qualitative interviews with Austrians, Spaniards, Germans and Hungarians, which were conducted from 1996 to 2001. This paper uses the cultural standard framework as its theoretical background as well as the concepts of team development. The emphasis of our research is on those culture standards that have been identified as relevant for the cooperation within teams. Critical Incidents that can be explained by the above-mentioned culture standards have been categorized referring to the Five-Phase-Model of team development by Tuckman and Jensen. – – In diesem Beitrag wird die Auswirkung österreichischer, spanischer, deutscher und ungarischer Kulturstandards auf die in Arbeitsgruppen relevanten Prozesse und auf die Performance in Arbeitsgruppen analysiert. Als empirische Datenbasis dienen 201 qualitative Interviews, die mit Österreichern, Deutschen, Ungarn und Spaniern zwischen 1996 und 2001 durchgeführt wurden. Das Kulturstandardkonzept sowie die Konzepte zur Teamentwicklung bilden den theoretischen Hintergrund. Der Fokus unserer Studie liegt auf jenen Kulturstandards, die für die Zusammenarbeit in Teams als relevant identifiziert wurden. Jene Kritische Interaktionssituationen, die mit den oben genannten Kulturstandards erklärt werden können, werden nach dem Phasen-Modell der Teamentwicklung nach Tuckman und Jensen kategorisiert.
Keywords: 650; Intercultural Teams; Intercultural Management; Intercultural Communication; Teamwork; Cultural Standard